-7x+9y = 54 9y = 7x+54 y = 7/9x+6 which is now in slope-intercept form
Slope-intercept form is y = mx + b5x + 9y = -36Subtract 5x from each side:9y = -5x - 36Divide everything by 9:y = -5/9x - 4
3x-3y=-9 and 9x-9y=-27 both simplifies to x-y=-3.
-3x+9y = 6 9y = 3x+6 y = 1/3x+2/3
Y-8x plus 9y equals 10y-8x.
x2 - y2 + 9x - 9y =(x2 + 9x) - (y2 + 9y) =x(x + 9) - y(y + 9)================================Another way to go after it:x2 - y2 + 9x - 9y =(x2 - y2) + 9x - 9y =(x + y) (x - y) + 9 (x - y) =(x + y + 9) (x - y)
The following is the answer.
9 + 9y = 27x -9 -9 9y = 27x - 9 9y/9 = 27x/9 - 9/9 y = 3x -1
This statement is already nearly factored. The best we can do is pull out the 9 from each term:9x + 9y + 72 = 9(x + y + 8)
36x-9y = 15 -9y = -36x+15 y = 4x-5/3 in slope intercept form
It can be simplified to: 9y-2x